Flowers: a potential source of human nutrition - Saurabh, Vivek; Barman , Kalyan (Journal of Postharvest Technology, 2020)
Flowers, besides its cultural significance were being consumed since ancient times in many cultures around the world. They were used in different  culinary preparations or in various dishes as garnish or trimmings. In recent years, interest in consumption of fresh flowers has been renewed due their  nutritional value and medicinal properties. A number of flowers such as rose, marigold, chrysanthemum, garden nasturtium, etc. can be consumed  either as fresh or after drying or freezing. Apart from proving new colours, flavours and texture to the food, these edible flowers also serve as a  potential source of several bioactive compounds like phenolics, flavonoids, pigments, etc. which exert very high antioxidant activity. These flowers also  contain several minerals, the content of which are comparable with that of the fruits and vegetables. Further, recent studies have revealed that being a  rich source of antioxidants, consumption of these flowers is effective as anti-inflammatory, antimicrobial, hepatoprotective, anticancer and antidiabetic  agents. Therefore, flowers can be utilized as a source of new and promising foodstuff for wide application in human nutrition.
Keywords: Edible flower; bioactive compound; medicinal value; nutrition